Investigation Structural Properties of Cu2ZnSnS4Thin Films Prepared by Pulse Laser Deposition - Ali J. Khalaf (Journal of Global Pharma Technology, 2016)
The prepared samples of thin-film by laser ablation method were achieved. Powders of (CZTS) copper (Cu), zinc (Zn), tin (Sn) and Sulfur (S) of and   then compressing by approximately 3 tons in Pellets form.  The samples were ablated by using Neodymium-YAG laser with different laser energies (400mJ, 500mJ, 600mJ, 700mJ, 800mJ) and number of pulses (300) pulse, frequency (6Hz) and wavelength (1064) nm obtained the plasma plume at 10-5mbar pressure. Results indicate by using XRD, AFM , SEM and EDX devices.by x-ray diffraction study of Cu2ZnSnS4 compound films prepared are proven to be  polycrystalline tetragonal as noted when the laser energy is increased when the process of ablation of the target CZTS  The grain size increases while the strain, the dislocation density  and the lattice constants (ao, co) decrease. Through the images of the atomic force microscope (AFM) it was observed that the grain size decreases from (CZTS400mJ-CZTS700mJ) and then increases. There is also an increase in the surface roughness rate and the square root rate (CZTS600mJ - CZTS800mJ) by increasing the laser energy when the process of ablation of the target CZTS with constant other laser parameters. Through scanning electron microscopy (SEM) images, the spherical shape of the nanoparticles is observed by increasing the laser energy when the process of ablation of the target CZTS with constant other laser parameters with irregular forms. The EDX test showed that the films contained Cu, Zn, Sn, S elements as expected, indicating the formation of high-purity CZTS films.Keywords: Structural, Thin film, Nanoparticle, CZTS, Composite, XRD, AFM, SEM, EDX, laser ablation.